Formation of Tetranuclear Nickel(II) Complexes with Schiff-Bases: Crystal Structures and Magnetic Properties - Zhonglu You; Yingying Luo; Susan Herringer; Yanmin Li; Silvio Decurtins; Karl W. Krämer; Shi-Xia Liu (Crystals, 2020)
The cubane-type structure is a typical representative of tetranuclear coordination compounds. In this work, two anionic Schiff-base ligands, (L1)2− and (L2)2−, each offering an O^N^O coordination pocket, ligate four NiII ions into a [Ni4O4] cubane core. The ligands are H2L1 = 2−[[(3-ethoxy-2−hydroxyphenyl) methylene]amino]benzenemethanol and H2L2 = 2−[[(5-fluoro-2−hydroxyphenyl)methylene]amino]benzenemethanol. In both compounds, [Ni4(L1)4(EtOH)4] (1) and [Ni4(L2)4(MeOH)4] (2), alkoxy oxygens of the ligands act in a bridging μ3-O binding mode. Magnetic susceptibility and magnetization data for compounds 1 and 2 are presented. The Ni–O–Ni bond angles of the cubane core determined from single crystal X-ray diffraction data play a key role for a magneto-structural correlation. Dominant intracube ferromagnetic behavior is observed, and the coupling parameters were determined for both compounds, leading to nonzero spin ground states in accordance with the broadly accepted bond angle guideline.